1979
DOI: 10.1099/0022-1317-45-3-611
|View full text |Cite
|
Sign up to set email alerts
|

The Structural and Infected Cell Polypeptides of Influenza B Virus

Abstract: SUMMARYStructural and virus-induced infected cell polypeptides of several strains of influenza B virus were examined by high resolution polyacrylamide gel electrophoresis and shown to be directly analogous to those of the influenza A viruses. Eight structural polypeptides, P1, P2, Ps, HAj, HA2, NA, NP and M were observed in purified virus and at least two additional polypeptides, HA and NS could be detected in infected MDCK cells. The three P proteins plus NP were shown to be associated with RNA-dependent RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Preparation of RNP from the A\X-31 virus was as previously described . RNP preparation from B\HK\HG reassortant virus was according to Almond et al (1979) with slight modification. Briefly, concentrated egg-grown virus was dissolved in disruption buffer containing 10 mM Tris-HCl (pH 7n4), 100 mM NaCl, 100 mM KCl, 50 mM MgCl # , 4 mM DTT, 1 % NP40 and 0n5 % lysolecithin.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of RNP from the A\X-31 virus was as previously described . RNP preparation from B\HK\HG reassortant virus was according to Almond et al (1979) with slight modification. Briefly, concentrated egg-grown virus was dissolved in disruption buffer containing 10 mM Tris-HCl (pH 7n4), 100 mM NaCl, 100 mM KCl, 50 mM MgCl # , 4 mM DTT, 1 % NP40 and 0n5 % lysolecithin.…”
Section: Methodsmentioning
confidence: 99%
“…Racaniello & Palese (1978 have demonstrated the migrational differences of N S 1 and M proteins between the B/Lee/40 and B/Maryland/59 strains. Almond et al (1979) have compared the proteins of four influenza B strains by SDS-PAGE, and have demonstrated that the mobility of NSI, NP and HA proteins are different among strains. In the present paper, we have also found migrational differences in HA, NA and NSI proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza B virus, like the influenza A virus, consists of the two surface glycoproteins, haemagglutinin (HA) and neuraminidase (NA) and the five internal non-glycosylated proteins, nucleoprotein (NP), matrix (M) protein and three P proteins (P1, P2, Pa) (Almond et al, 1979). The HA glycoproteins may be present in virions as two cleavage products, HA 1 and HA 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza B virus has no distinct subtypes because of homology but is separated into two lineages, Yamagata and Victoria, based on different antigenicities (3). The genome of influenza B virus is composed of eight negative-sense singlestranded RNA segments encoding 11 viral proteins: HA, NA, PA, PB1, PB2, NP, M1, M2, NEP, NB, and NS1 (4,5). Their functions in viral infection cycles have been generally characterized.…”
mentioning
confidence: 99%